2007
DOI: 10.1111/j.1469-8749.2007.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

West syndrome in an infant with vitamin B12 deficiency in the absence of macrocytic anaemia

Abstract: Vitamin B12 deficiency in infants often produces haematological and neurological deficits, including macrocytic anaemia, neurodevelopmental delay or regression, irritability, weakness, hypotonia, ataxia, apathy, tremor, and seizures. The diagnosis of vitamin B12 deficiency can be difficult when the typical macrocytic anaemia is absent. We report the case of a 10‐month‐old female diagnosed with West syndrome associated with vitamin B12 deficiency but without macrocytic anaemia caused by nutritional inadequacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 9 publications
0
42
1
1
Order By: Relevance
“…Epilepsy has been described as a rare manifestation of infantile vitamin B12 deficiency [4,6,9,14]. Moreover, there are isolated reports on an association with infantile spasms syndrome (ISs) and its subset West syndrome [2,7,8]. The latter describes an age-related triad of epileptic spasms, characteristic EEG findings and developmental regression [3,4,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy has been described as a rare manifestation of infantile vitamin B12 deficiency [4,6,9,14]. Moreover, there are isolated reports on an association with infantile spasms syndrome (ISs) and its subset West syndrome [2,7,8]. The latter describes an age-related triad of epileptic spasms, characteristic EEG findings and developmental regression [3,4,14].…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy has been reported as a rare manifestation of vitamin B12 deficiency. Moreover, few reports have described a causal relationship with manifestation of West syndrome [2,4,7,8]. Although vitamin B12 supplementation often results in rapid improvement of initial hematological and neurological findings, concern has been raised regarding long-term development [2,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Erol et al (11) reported that mental-motor development which was normal until the age of nine months paused with initiation of seizures in this 10-month-old female patient. No pathology was found on physical examination except for apathy, hypotony and reduced deep tendon reflexes.…”
Section: Discussionmentioning
confidence: 63%
“…However, vitamin B 12 deficiency is thought to cause imbalance between the growth factors influencing the central nervous system and neurotoxic cytokines, and increased lactate, glutamate and excitatory amino acids (26)(27)(28). There- (29)(30)(31)(32)(33)(34). We encountered central nervous system signs and symptoms especially in rapidly growing infants in the early period between 2 and 18 months.…”
Section: Discussionmentioning
confidence: 99%